Integrated Examines of Hydrolyzers, Compression Ratio, Spark Plugs, and Ethanol Gasoline in Four Stroke Spark Ignition Engine for Potentially Application of Higher Ethanol Application - Wawan Purwanto; Hasan Koten; Hasan Maksum; Dwi Sudarno Putra; Anang Baharuddin Sahaq (Automotive Experiences, 2026)
Optimizing combustion parameters by incorporating alternative fuels and modifying the engine's mechanical properties is essential to improving the thermal efficiency and performance of modern internal combustion engines. This study examines the impact of HHO gas utilization, variations in compression ratios, various types of spark plugs, and ethanol gasoline blends on the torque and other characteristics of a 4-stroke fuel-injected single cylinder engine. Hydrogen is generated via electrolysis and used as a supplementary fuel. The Taguchi method was employed to create tests involving four variables: HHO percentage, compression ratio, spark plug type, and ethanol mixture. Testing occurred at 5000 RPM under a load of 1800 Watts. The findings indicated that the combination of 20% HHO, a compression ratio of 16.9:1, platinum spark plugs, and E-80 ethanol yielded optimal engine performance, with thermal efficiency reaching 60% at 7500 rpm. Moreover, the results of deposit content analysis after 50 hours of operation indicated that the ideal design produced fewer deposits than RON 92 gasoline.